MIC and MBC Levels of Combination Camellia Sinensis and Mentha Piperita Extract Mouthwash Against Streptococcus Mutans - Yuani Setiawati; Muflikhah Ramadhani; Jihan Bobsaid; Dennia Oktavia Zahidah Hulwah (Faculty of Medicine, Hasanuddin University., 2022)
Introduction: Awareness of Indonesian people in maintaining dental and oral health is low, proved by an increase in the percentage of dental and oral health problems by 2.7%. Caries is a dental and oral health problem that occurs in many children. The main cause of dental caries is Streptococcus mutans. To solve this problem, it is necessary to use herbal mouthwash made from a combination of Camellia sinensis and Mentha piperita extract as an antibacterial against Streptococcus mutans. Methods: Mouthwash is made through several processes namely plant determination, extraction, and mouthwash making. Minimal Inhibitory Concentration (MIC) is determined by diluted methods, Minimal Bactericidal Concentration (MBC) is determined by the agar streaking method, and colony tests are calculated using colony counters. Results: The result of plant determination showed the plants in this study were Camellia sinensis and Mentha piperita. At a concentration of 6.25%, no growth of bacteria in each repetition with the number of colonies 0 CFU / ml. While at a concentration of 3.125% found the average number of colonies 13 CFU / ml. Conclusions: Based on good MIC and MBC results, mouthwash containing Camellia sinensis and Mentha piperita has been shown to kill and inhibit the growth of Streptococcus mutans bacteria